The psychometric testing of the Nursing Teamwork Survey in Iceland - Bragadóttir, Helga; Kalisch, Beatrice J.; Smáradóttir, Sigríður Bríet; Jónsdóttir, Heiður Hrund (International Journal of Nursing Practice, 2016)
Peer Reviewed https://deepblue.lib.umich.edu/bitstream/2027.42/136495/1/ijn12422_am.pdf https://deepblue.lib.umich.edu/bitstream/2027.42/136495/2/ijn12422.pdf